La disfuncionalidad familiar y su incidencia en la adaptación escolar de los estudiantes del 5to año de educación básica de la unidad educativa Juan E. Verdesoto del cantón Babahoyo de la Provincia los Ríos del periodo lectivo 2015-2016 - Vera Olea, Luis Horacio (2016)
The family is the first responsible for the education of children; on this basis is presented grade work, which took place in the Education Unit Juan E. Verdesoto Cantón Babahoyo, where a family dysfunctionality, consequently resulting in poor school adjustment occurs. The study is to analyze the factors that lead to inappropriate behavior, reactions and changes child following their incorporation into school for the problems in their family home. For these reasons it is necessary to say that the child to join the school must have family participation in all possible areas, to achieve adaptation properly. The research is descriptive-explanatory, thus revealing the importance leads to discover the family relationship, its factors or emotional ties in the development of social skills and relationships of the environment in education.